Violence against health workers in Family Medicine Centers - Al-Turki N; Afify AAM; AlAteeq M (Journal of Multidisciplinary Healthcare, 2016)
Nouf Al-Turki,1 Ayman AM Afify,1 Mohammed AlAteeq2 1Family Medicine Department, Prince Sultan Military Medical City, 2Department of Family Medicine and PHC, King Abdul-Aziz Medical City, National Guard Health Affairs, Riyadh, Kingdom of Saudi Arabia Background: Health care violence is a significant worldwide problem with negative consequences on both the safety and well-being of health care workers as well as workplace activities. Reports examining health care violence in Saudi Arabia are limited and the results are conflicting.Objective: To estimate the prevalence and determine the demographic and occupational characteristics associated with workplace violence in primary care centers in Riyadh, Saudi Arabia.Methods: A cross-sectional study included 270 health care workers in 12 family medicine centers in Riyadh during November and December 2014. A structured self-administered questionnaire was used to estimate the frequency, timing, causes, reactions, and consequences of workplace violence plus participants’ demographic and occupational data.Results: A total 123 health care workers (45.6%) experienced some kind of violence over 12 months prior to the study. These included physical (6.5%) and nonphysical violence (99.2%), including verbal violence (94.3%) and intimidation (22.0%). Offenders were patients (71.5%) in the majority of cases, companions (20.3%), or both (3.3%). Almost half (48.0%) of health care workers who experienced violence did nothing, 38.2% actively reported the event, and 13.8% consulted a colleague. A significant association of workplace violence was found with working multiple shifts, evening or night shift, and lack of an encouraging environment to report violence.Conclusion: Workplace violence is still a significant problem in primary care centers. The high frequency of violence together with underreporting may indicate the inefficiency of the current safety program. More safety programs and training activities for health care workers, efficient reporting system, and zero tolerance policies need to be implemented to minimize workplace violence against health workers. Keywords: health care workers, violence, primary health care, Saudi Arabia, workplace violence, assaults